Long non-coding RNA SNHG22 facilitates hepatocellular carcinoma tumorigenesis and angiogenesis via DNA methylation of microRNA miR-16-5p. Issue 1 (1st January 2021) - Zhang, Yinxin; Lu, Changliang; Cui, Haiwei
ABSTRACT: Hepatocellular carcinoma (HCC) is considered as a common malignancy worldwide. Considerable evidence has illustrated that abnormally expressed long noncoding RNAs (lncRNAs) are in a close correlation with the initiation and progression of various tumors, including HCC. LncRNA small nucleolar RNA host gene 22 (SNHG22) has been reported to play important roles in tumor initiation, but its role and mechanism are little known in HCC. In our report, we discovered the high level of SNHG22 in HCC tissues and cells, and the high expression of SNHG22 was correlated with unfavorable clinical outcome in HCC patients. Functional assays implied that SNHG22 deficiency suppressed cell proliferation, migration, invasion, and angiogenesis in vitro. Additionally, it was also confirmed that silenced SNHG22 suppressed tumor growth and angiogenesis in vivo. Mechanistic exploration revealed that SNHG22 recruited DNMT1 to miR-16-5p DNA promoter through EZH2 and inhibited miR-16-5p transcription via DNA methylation. Finally, we verified that the suppression of miR-16-5p countervailed the suppressive effect of SNHG22 deficiency on HCC cell proliferation, migration, invasion, and angiogenesis. Conclusively, this study clarified the SNHG22/EZH2/DNMT1/miR-16-5p axis and revealed that SNHG22 could be an underlying biomarker for HCC.